Physiologically gated microbeam radiation using a field emission x‐ray source array. Issue 8 (10th July 2014) - Chtcheprov, Pavel; Burk, Laurel; Yuan, Hong; Inscoe, Christina; Ger, Rachel; Hadsell, Michael; Lu, Jianping; Zhang, Lei; Chang, Sha; Zhou, Otto
Abstract : Purpose: Microbeam radiation therapy (MRT) uses narrow planes of high dose radiation beams to treat cancerous tumors. This experimental therapy method based on synchrotron radiation has been shown to spare normal tissue at up to 1000 Gy of peak entrance dose while still being effective in tumor eradication and extending the lifetime of tumor‐bearing small animal models. Motion during treatment can lead to significant movement of microbeam positions resulting in broader beam width and lower peak to valley dose ratio (PVDR), which reduces the effectiveness of MRT. Recently, the authors have demonstrated the feasibility of generating microbeam radiation for small animal treatment using a carbon nanotube (CNT) x‐ray source array. The purpose of this study is to incorporate physiological gating to the CNT microbeam irradiator to minimize motion‐induced microbeam blurring. Methods: The CNT field emission x‐ray source array with a narrow line focal track was operated at 160 kVp. The x‐ray radiation was collimated to a single 280 μ m wide microbeam at entrance. The microbeam beam pattern was recorded using EBT2 Gafchromic © films. For the feasibility study, a strip of EBT2 film was attached to an oscillating mechanical phantom mimicking mouse chest respiratory motion. The servo arm was put against a pressure sensor to monitor the motion. The film was irradiated with three microbeams under gated and nongated conditions and the full width at half maximums and PVDRs were compared. An in vivo study was also performed with adult male athymic mice. The liver was chosen as the target organ for proof of concept due to its large motion during respiration compared to other organs. The mouse was immobilized in a specialized mouse bed and anesthetized using isoflurane. A pressure sensor was attached to a mouse's chest to monitor its respiration. The output signal triggered the electron extraction voltage of the field emission source such that x‐ray was generated only during a portion of the mouse respiratory cycle when there was minimum motion. Parallel planes of microbeams with 12.4 Gy/plane dose and 900 μ m pitch were delivered. The microbeam profiles with and without gating were analyzed using γ ‐H2Ax immunofluorescence staining. Results: The phantom study showed that the respiratory motion caused a 50% drop in PVDR from 11.5 when there is no motion to 5.4, whereas there was only a 5.5% decrease in PVDR for gated irradiation compared to the no motion case. In the in vivo study, the histology result showed gating increased PVDR by a factor of 2.4 compared to the nongated case, similar to the result from the phantom study. The full width at tenth maximum of the microbeam decreased by 40% in gating in vivo and close to 38% with phantom studies. Conclusions: The CNT field emission x‐ray source array can be synchronized to physiological signals for gated delivery of x‐ray radiation to minimize motion‐induced beam blurring. Gated MRT reduces valley dose between lines during long‐time radiation of a moving object. The technique allows for more precise MRT treatments and makes the CNT MRT device practical for extended treatment.